1983
DOI: 10.1111/j.1365-2044.1983.tb06534.x
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative morbidity following gynaecological outpatient Iaparoscopy. A reappraisal of the service

Abstract: Summary Fifty‐six women having out‐patient gynaecological laparoscopies were studied to determine anasthetic problems and postoperative morbidity. It is concluded that the procedure is safe, and although the postoperative morbidity appears high it is very acceptable to the patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

1984
1984
2000
2000

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…Pain after laparoscopy does not seem to be related to the volume of gas used during the operation. We use a relatively large volume but pain was less frequent than reported by others (Collins et al 1984), possibly due to our usual practice of compressing the abdomen manually to expel excess gas through the open laparoscopy cannula at the end of the operation. The further marked benefit of a gas drain postoperatively suggests that visceral peristaltic and voluntary muscle activity leads to expulsion of a further considerable volume.…”
Section: Discussionmentioning
confidence: 82%
“…Pain after laparoscopy does not seem to be related to the volume of gas used during the operation. We use a relatively large volume but pain was less frequent than reported by others (Collins et al 1984), possibly due to our usual practice of compressing the abdomen manually to expel excess gas through the open laparoscopy cannula at the end of the operation. The further marked benefit of a gas drain postoperatively suggests that visceral peristaltic and voluntary muscle activity leads to expulsion of a further considerable volume.…”
Section: Discussionmentioning
confidence: 82%
“…The pain usually reaches its maximum 24 hours postoperatively before it declines gradually.1 This shoulder pain was found to be similar to, but less severe than, that produced when using suxamethonium in anesthesia. 1 Following the introduction of laparoscopic surgery, shoulder pain was reported in randomized studies to be more common than after laparotomy incisions.19 An incidence as high as 42% was reported.20 In retrospective studies, however, it was either not reported2-5 or reported as a rarity, with figures as low as 0.8%6,21 Residual CO2 in the pneumoperitoneum was blamed for the pain. The gas is thought to act either by its irritant effect on the peritoneum and phrenic nerve.1,8-10 or by creating a space between the liver and the diaphragm, leading to loss of the suction effect on the liver by the diaphragm with increased traction on the triangular and coronary ligaments.11,12,22 However, the results coming from different studies regarding the role of residual CO2 are controversial.…”
Section: Resultsmentioning
confidence: 99%
“…The nausea, vomiting, and/or retching is a source of significant discomfort following laparoscopic cholecystectomy, and patients with significant gastrointestinal dysfunction should usually be admitted to the hospital for observation and comfort [7,15,23,29,34]. Only two of our patients required readmission for nausea, vomiting, and dehydration, with no significant sequelae.…”
Section: Case #/--Patient Ehmentioning
confidence: 96%